I would like to solve the below optimization problem. Any hints is appreciated. I'm gussing the answer is 1. \begin{equation} \begin{aligned} & \min \prod_{i=1}^{i=3}\left(\frac{1+x+ay}{1+x_i+ay_i}\right)^{p_i} \\ & \operatorname{s.t.} & & \sum_{i=1}^{3}p_i =1, \\ &&& \sum_{i=1}^{3} p_ix_i \le x, \\ &&& \sum_{i=1}^{3} p_iy_i \le y,\\ &&&p_i\ge 0, \; x_i\ge 0, \;y_i\ge 0,\; x> 0, \;y >0. \end{aligned} \end{equation} in which $p_i, x_i$, and $y_i$ are variables and $a$, $x$, and $y$ are constant.

  • $\begingroup$ $ x $ and $ y $ are greater than 0. $\endgroup$
    – Bob
    Sep 21, 2015 at 19:29
  • $\begingroup$ Well, The quotient needs to be min., so the Denominator needs to be max. so $x_i+ay_i$ needs to be max. The answer of 1 sounds true, but I guess you need a numerical algorithm for this one. $\endgroup$
    – NoChance
    Sep 21, 2015 at 22:42
  • $\begingroup$ You need to tell us what are the variables and what are the constants. $\endgroup$ Sep 21, 2015 at 23:22
  • $\begingroup$ $p_i, x_i$, and $y_i$ are variables and $a$, $x$, and $y$ are constant. $\endgroup$
    – Bob
    Sep 21, 2015 at 23:42
  • 1
    $\begingroup$ Numerical test indeed indicates that the optimal solution is $x_i = x, y_i = y, p_i = 1/3$. $\endgroup$ Sep 22, 2015 at 6:41

1 Answer 1


We find the minimum of a more general expression

$$E=\prod_{i=1}^{n}\left(\frac{1+x+ay}{1+x_i+ay_i}\right)^{p_i},$$ where we substituted the number $3$ by for any natural number $n$. If some of our $p_i$’s are zero, we can drop them and diminish $n$. Also we recall Weighted AM-GM inequality: Let $p_1,\dots, p_n$ and $t_1,\dots, t_n$ be positive number such that $\sum_{i=1}^n p_i=1$. Then

$$\sum_{i=1}^n p_it_i\ge \prod_{i=1}^n t_i^{p_i}.$$

Now we remark that the problem to find a minimum of $E$ is equivalent to the problem to to find a maximum of $E^{-1}$. But

$$E^{-1}=\prod_{i=1}^{n}\left(\frac{1+x_i+ay_i}{1+x+ay}\right)^{p_i}=$$ $$\prod_{i=1}^{n}\left(1+x_i+ay_i\right)^{p_i}\left(\prod_{i=1}^{n}\left(1+x+ay\right)^{p_i}\right)^{-1}=$$ $$\prod_{i=1}^{n}\left(1+x_i+ay_i\right)^{p_i}\left(1+x+ay\right)^{-\sum_{i=1}^n p_i}=$$ $$\prod_{i=1}^{n}\left(1+x_i+ay_i\right)^{p_i}\left(1+x+ay\right)^{-1}.$$

But by Weighted AM-GM inequality $$\prod_{i=1}^{n}\left(1+x_i+ay_i\right)^{p_i}\le \sum_{i=1}^n p_i(1+x_i+ay_i)\le 1+x+ay.$$

So $E^{-1}\le 1$ and the equality is attained, for instance when all $x_i$’s are equal to $x$, all $y_i$’s are equal to $y$, and all $p_i$’s are equal to $1/n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.